Occult Nasopharyngeal Foreign Bodies in Children: Lessons from Clinical Experience and Published Evidence - Hawa Mohamed Saad (African Journal of Advanced Pure and Applied Sciences, 2026)
Background: Foreign body aspiration is a common pediatric emergency; however, nasopharyngeal impaction following choking episodes is rare and frequently overlooked. Normal chest imaging and misleading clinical histories may delay diagnosis, increasing the risk of complications. Objective: To highlight the diagnostic challenges associated with occult nasopharyngeal foreign bodies in children following choking episodes through presentation of a pediatric case and review of previously published literature. Methods: A retrospective review of a pediatric case of nasopharyngeal foreign body impaction managed at Ibn-Sina Teaching Hospital, Sirte, Libya, was conducted. Clinical presentation, diagnostic course, imaging findings, treatment, and outcomes were analyzed and compared with five previously published pediatric cases identified through literature review. Results: Six pediatric cases (one institutional case and five published cases) were reviewed. Common diagnostic features included misleading caregiver history, normal chest examination and radiographs, delayed onset of upper airway symptoms, and prolonged diagnostic delay. Persistent nasal obstruction, rhinorrhea, and snoring were the most frequently reported manifestations leading to eventual diagnosis. Conclusion: Nasopharyngeal foreign bodies represent an underrecognized cause of persistent upper airway symptoms following pediatric choking episodes. In children with ongoing nasal symptoms despite normal chest findings, evaluation of the nasopharynx should be considered to facilitate early diagnosis and prevent potentially serious complications.